Improving Just – in –Time Manufacturing in Voltage Regulator Assembly Line using RFID System - N K, Sachin; S Shivakumara, B; Sridhar, V (International Journal of Engineering and Technology, 2018)
In a progressively digital world, manufacturing innovativeness are deal with with a complex, dynamic and reasonable environment due to globalization and a prompt progress of information and communication technologies. Just in time (JIT) manufacturing is one of the most important tactics used to increase manufacturers’ effectiveness through lead time, SAP conformation and inventory reduction. This paper deals with the material management strategy that uses production Kanban to signal the need for replenishment of selected product from prefers suppliers to site and also to optimize the flow of work through the RFID system to increase the business value delivery and it is also an evolutionary change approach for an organization to be adequate for its purpose in service delivery.